Political codes analysis: fundamentals and perspectives - Andrushko, Vladyslav (Eximia, 2022)
This essay asks how we might enrich modern political discourse analysis. To do so, I propose a political codes analysis as a complementary approach, as a way of investigating a social world using the special concepts of codes and programs. The essay is divided into two sections. The first section aims to integrate the concepts of codes and programs into modern political analysis. Here, I examine the possibility of using such terms in the humanities and define them and describe their main features. The second section pays attention to the practical value of political codes analysis, focusing on the symbolic formalizing, technical features, and perspectives of further research. In this section, I consider Big Data and Blockchain technologies and how they might be integrated into political discourse analysis. The main purposes of political codes analysis are to find identities (ideologies), to disclose potential political conflicts and to investigate a subject and an object of political power. The essay may be of interest both to discourse analysts and other scholars who study social processes.